Characterization of Pandanus amaryllifolius Roxb via Fourier-Transformed Infrared FTIR Spectrogram - Abdullah, M. Z (2012)
Pandanus amaryllifolius Roxb or pandan leaves are commonly used in the South Asian and South East Asian region as food coloring and flavoring agents. The plant is also being utilized as fragrance due to its aromatic scents as well as in the medicinal purposes to cure fever. Yet, its potential as an adsorbent in the heavy metal remediation and wastewater treatment has not being widely reported in the literature. Due to the possible mechanisms such as adsorption, ion exchange and/or chelation between biomass and the metal ions, it is significant to characterize the presence of specific chemical groups that exist on the wall of the leaves that contributes to the uptake process. In order to confirm the viability of the numerous chemical groups such as the carboxyl, hydroxyl, amide and ether, FTIR was used to characterize the raw P. amaryllifolius Roxb. The information provides insight on the possible sorption mechanism that will occur between the metal cations and the biomass during the biosorption process.